Single- Versus Dual-Access Transcatheter Aortic Valve Implantation Using Balloon-Expandable Platform - Muntaser Omari, MD; Mario E. Diaz Nuila, MD; Ahmed Abdalwahab, MD; Debbie Stewart, BSc; Richard Edwards, MD; Rajiv Das, MD; Azfar Zaman, MD; Mohamed Farag, MD; Mohammad Alkhalil, MD (JACC: Advances)
Background: Vascular complications are more frequently encountered in patients undergoing transcatheter aortic valve implantation (TAVI) compared to surgical aortic valve replacement. Single access (SA) TAVI may reduce access-site complications, but this approach has not been widely studied. Objectives: The aim of the study was to compare clinical outcomes of SA vs dual access (DA) TAVI using balloon-expandable valve Sapien 3 Ultra. Methods: This was a retrospective analysis of consecutive patients who underwent TAVI using balloon-expandable valve. Data were prospectively entered into a dedicated web-based database. The co-primary endpoints were device success and 30-day safety endpoints, defined according to the Valve Academic Research Consortium 3. A propensity score matching with a 1:1 ratio was performed comparing SA vs DA TAVI. Results: Of 532 patients who had transfemoral TAVI, 117 (22%) underwent the SA approach. Propensity score matching analysis yielded a well-balanced 204 patients (102 in each group). SA was associated with a significant reduction in contrast use, fluoroscopy time, radiation exposure, and total procedure time. Device success was comparable between the 2 groups (3.9% vs 3.9%; OR: 1.00; 95% CI: 0.24-4.11; P > 0.99). The 30-day safety profile of the Valve Academic Research Consortium 3 was significantly better in patients who underwent SA vs DA TAVI (15.0% vs 28.9%; OR: 0.44; 95% CI: 0.22-0.88; P = 0.02). This was derived from a lower incidence of severe paravalvular regurgitation and new pacemaker implantation. Conclusions: SA is a feasible and safe strategy compared to DA TAVI. It was associated with quicker procedure times, lower contrast and radiation exposure, and a better 30-day safety profile than the DA strategy. Future randomized studies are needed to further assess this strategy.